Investigation of the interaction of deuterium with Sn73Li27 tin-lithium alloy - T. Kulsartov; I. Kenzhina; Yu Ponkratov; Yu Gordienko; Zh Zaurbekova; K. Samarkhanov; S. Askerbekov; Ye A. Kenzhin; A.B. Yelishenkov (Nuclear Materials and Energy)
The SnLi alloy has good prospects to be used as a material of intra-chamber elements of fusion facilities, as it has a number of advantages over pure lithium. The results of a series of experiments on deuterium adsorption/desorption by a Sn73Li27 alloy sample are presented. To prepare an alloy sample with the required tin and lithium content, a technique was developed and a special experimental device was constructed. An ampoule device was manufactured to conduct a series of experiments to study sample saturation with deuterium and desorption of deuterium and deuterium-containing molecules from it. Saturation was carried out at alloy temperatures of 650, 600, 550, 500 and 450 °C. TDS experiments were carried out at 20 °C/min. The possible mechanism of deuterium dissolution and release from the tin-lithium alloy was considered and temperature dependences of the effective deuterium solubility constant KS in the tin-lithium alloy were calculated within the framework of the proposed mechanism. The temperature dependence of the Sieverts’ constant for the test sample in the temperature range of 500–650 °C was determined as KST=3.6·106∙exp-32400(J)RT∙Pa12.